2012
DOI: 10.1038/nnano.2012.187
|View full text |Cite
|
Sign up to set email alerts
|

A nanocomposite ultraviolet photodetector based on interfacial trap-controlled charge injection

Abstract: Ultraviolet photodetectors have applications in fields such as medicine, communications and defence, and are typically made from single-crystalline silicon, silicon carbide or gallium nitride p-n junction photodiodes. However, such inorganic photodetectors are unsuitable for certain applications because of their high cost and low responsivity (<0.2 A W(-1)). Solution-processed photodetectors based on organic materials and/or nanomaterials could be significantly cheaper to manufacture, but their performance so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
530
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 664 publications
(548 citation statements)
references
References 27 publications
13
530
2
3
Order By: Relevance
“…Minimization of dark current is imperative, as this limits the minimum detectable power and also the dynamic range of the HPD, as the on/off ratio can be enhanced by reducing the dark current [15]. When compared to other HPD devices in the literature, the HPD in Figure 2 exhibits relatively low dark current [16].…”
Section: Photodiode Characterisationmentioning
confidence: 99%
“…Minimization of dark current is imperative, as this limits the minimum detectable power and also the dynamic range of the HPD, as the on/off ratio can be enhanced by reducing the dark current [15]. When compared to other HPD devices in the literature, the HPD in Figure 2 exhibits relatively low dark current [16].…”
Section: Photodiode Characterisationmentioning
confidence: 99%
“…Recently, Guo et al have shown that the electrons transferred from the polymer to the QD are trapped in the QD and under illumination those electrons shift to the LUMO energy level of the polymer and align the Fermi energy level of the active layer with that of the cathode [8]. This explanation is supported by (i) the lifetime measurements performed in this study; both in solution and film phase the AV value of ADS231BE was not effected from the increase in Zn 0.71 Cd 0.29 S concentration (Table 2) 365 nm UV illumination.…”
Section: The Electrical Characteristics Of Uv-pdmentioning
confidence: 99%
“…In recent years, due to the possibility to change the photo physical properties through simplified chemical synthesis and easy thin film processing, quantum dots (QD) and polymer:QD hybrids attract a lot of attention in UV-PD applications [1][2][3][4][5][6][7][8], as well as the other photonic applications, such as biological imaging and contrast agents [9,10], light-emitting devices (LEDs) [11,12] photovoltaic [13][14][15], etc. Most of the QDs used in UV-PDs are binary systems, the band gap of which are tuned by varying the diameter of the nanoparticle [1][2][3][4][5]7,8,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations